DAMPAK PERUBAHAN BIODATA AKTA NIKAH DAN AKIBAT HUKUMNYA TERHADAP ANAK - Isti Sulistyorini (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
According to Article 2 paragraph (2) of Law no. 1 Year 1974 concerning marriage states every marriage must be registered for the existence of Legality of Law. Sometimes there is a mistake in recording, either because the element of intent or mistakenness, this result of biodata error in the marriage certificate, will cause difficulties in the birth certificate, which will have legal impact on the rights of the child. The method used in this study is the method of sociological juridical approach is a study that emphasizes the Law Science, also see the reality prevailing in society. Sampling method used is Purpose Sampling method is a sample taken on the basis of subjective researcher. To guarantee the rights of the child, marriage biodata must be changed by a court decision. The impact of biodata change of marriage certificate will be followed by the change of  birth certificate. Birth certificates are  an  authentic proof of  the  legal relationship between parents and children, which will have an impact on children's rights related to legislation.